2017
DOI: 10.1504/ijtgm.2017.082376
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of risk disclosure in the Indonesian non-listed banks

Abstract: The study aims to explain the extent of risk disclosure of Indonesian non-listed banks' annual reports and to investigate the determinants which drive non-listed banks to disclose their risk. Risk disclosure is measured by Indonesian risk keywords divided by total number of sentences in annual reports. The result showed that total number of risk keyword, sentences and risk disclosure in annual reports has an upward trend. Leverage and profitability have negative association with risk disclosure. Aggregated fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
3
10
0
1
Order By: Relevance
“…Most studies indicate that disclosure is prevalent in large firms (e.g., Linsley & Shrives, 2006;Amran et al, 2009;Dobler et al, 2011;Elzahar & Hussainey, 2012;Miihkinen, 2012, Al-Shammari, 2014. However, Aryani and Hussainey (2017) report a nonsignificant association between firm size and CRD in Indonesia.…”
Section: Firm Size Ifrss' Adoption and Crdmentioning
confidence: 93%
“…Most studies indicate that disclosure is prevalent in large firms (e.g., Linsley & Shrives, 2006;Amran et al, 2009;Dobler et al, 2011;Elzahar & Hussainey, 2012;Miihkinen, 2012, Al-Shammari, 2014. However, Aryani and Hussainey (2017) report a nonsignificant association between firm size and CRD in Indonesia.…”
Section: Firm Size Ifrss' Adoption and Crdmentioning
confidence: 93%
“…First, researchers may need to use a firmer treatment to control the emotional effects. Second, this study can be improved by considering non-economic events (Gunaasih and Nursasmito, 2015) and risk disclosure (Aryani and Hussainey, 2017) as part of sequential information.…”
mentioning
confidence: 99%
“…This finding is also supported by the fact that, in an emerging region such as the GCC, where ownership concentration is widespread, government ownership is an essential element that encourages higher levels of corporate governance disclosures. Nevertheless, Aryani and Hussainey (2017) and Saggar and Singh (2017) reported a negative association between the number of block holders and risk disclosure. Finally, Table 7 indicates that there is no statistically significant relationship between the adoptions of IFRS and CCRD.…”
Section: Regression Results: Determining Factors Of Risk Disclosurementioning
confidence: 90%
“…In several recent studies this positive association between the firm size and the level of disclosure has been the subject of a consensus (Grassa et al, 2020;Augustina & Apriyanto, 2020). While other studies have concluded that there was no significant association between the level of risk disclosure and the firm size (Aryani & Hussainey, 2017;Anggraini & Dura, 2021). The following hypothesis is thus proposed: H 1: The extent of risk disclosure is positively associated with bank size.…”
Section: Level Of Risk Disclosure and Size Effectmentioning
confidence: 88%